Keabsahan Penempatan Anggota TNI Aktif dalam Menduduki Jabatan Sipil - Gratsia, Melani Ema; Supriyadi, Supriyadi; Nurita, Risky Febria; Amrullah, Moh. Fahrial; Rifandana, Raditya Feda (Bhirawa Law Journal, 2023)
This research is about the validity of the placement of active TNI members in civilian positions. Based on Article 47 of Law Number 34 of 2004 concerning the Indonesian National Army. There are concerns about the return of the dual function that the Indonesian people have long abandoned, which could harm the spirit of reform, democracy and affect the professionalism of the TNI in being a tool for national defense. The case approach for this research is the appointment of General Andi Chandra Assadudin (Active TNI Officer) as Acting Regent of West Seram, Maluku. Based on SK. Minister of Home Affairs Number 131.81-1164. The aim of this research is to determine and analyze the validity and exceptions to the provisions that provide gaps in the placement of Active TNI members in civilian positions. This research uses a type of normative legal research. The method used is a juridical-normative problem approach with a statutory approach (Statute Approach) and a case approach (Case Approach). Then the legal materials for this thesis research are through literature review obtained from primary legal materials in the form of statutory regulations, secondary legal materials in the form of legal books, legal journals, articles, papers, theses, theses and tertiary legal materials in the form of encyclopedias and library materials. which supports research.